HIF1A inhibitor PX-478 reduces pathological stretch-induced calcification and collagen turnover in aortic valve - Md Tausif Salim; Nicolas Villa-Roel; Booth Vogel; Hanjoong Jo; Ajit P. Yoganathan; Ajit P. Yoganathan (Frontiers in Cardiovascular Medicine, 2022)
HIF1A is significantly upregulated in calcified human aortic valves (AVs). Furthermore, HIF1A inhibitor PX-478 was shown to inhibit AV calcification under static and disturbed flow conditions. Since elevated stretch is one of the major mechanical stimuli for AV calcification, we investigated the effect of PX-478 on AV calcification and collagen turnover under a pathophysiological cyclic stretch (15%) condition. Porcine aortic valve (PAV) leaflets were cyclically (1 Hz) stretched at 15% for 24 days in osteogenic medium with or without PX-478. In addition, PAV leaflets were cyclically stretched at a physiological (10%) and 15% for 3 days in regular medium to assess its effect of on HIF1A mRNA expression. It was found that 100 μM (high concentration) PX-478 could significantly inhibit PAV calcification under 15% stretch, whereas 50 μM (moderate concentration) PX-478 showed a modest inhibitory effect on PAV calcification. Nonetheless, 50 μM PX-478 significantly reduced PAV collagen turnover under 15% stretch. Surprisingly, it was observed that cyclic stretch (15% vs. 10%) did not have any significant effect on HIF1A mRNA expression in PAV leaflets. These results suggest that HIF1A inhibitor PX-478 may impart its anti-calcific and anti-matrix remodeling effect in a stretch-independent manner.